2015
DOI: 10.1155/2015/835979
|View full text |Cite
|
Sign up to set email alerts
|

Liver Dysfunction Associated with Intravenous Methylprednisolone Pulse Therapy in Patients with Graves’ Orbitopathy

Abstract: Intravenous methylprednisolone (IVMP) pulse therapy is the first-line treatment for the active phase of moderate to severe Graves' orbitopathy (GO). However, acute and severe liver damage has been reported during and after IVMP therapy. In this retrospective study, we investigated risk factors for liver dysfunction during and after IVMP therapy based on 175 Japanese patients with moderate to severe GO and treated at our center between 2003 and 2011. The results showed that seven patients developed severe liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Adverse events associated with GC include weight gain, gastrointestinal side effects, glucose intolerance, thin skin and/or osteoporosis . The most common severe side effect is hepatotoxicity . Other severe adverse effects included cardiovascular complications .…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events associated with GC include weight gain, gastrointestinal side effects, glucose intolerance, thin skin and/or osteoporosis . The most common severe side effect is hepatotoxicity . Other severe adverse effects included cardiovascular complications .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, acute and severe liver damage were reported after IVMP pulse therapy [37]. In addition, the preexisting infection with viral hepatitis, such as HBV, was significantly associated with liver dysfunction [38]. In our study, patients who had detectable serum HBV DNA showed different degrees of liver damage after receiving therapy with high doses of corticosteroids.…”
Section: Discussionmentioning
confidence: 47%
“…To our concern, a limited number of cases of IVMPinduced hepatotoxicity in MS patients have been reported [2,[7][8][9][10]. In patients at risk, there has been proposed a strict monitoring of liver function once a week during pulse therapy, and once a month for the subsequent 12 months [4]. Considering our cases, and the literature review, we propose an additional liver surveillance in…”
Section: Discussionmentioning
confidence: 93%